Enhancing pro-environmental behavior through nature-contact environmental education: an empirical analysis based on randomized controlled experiment design - Zhao, Yupan; Liu, Xuanchang; Han, Xiao (Frontiers in Environmental Science, 2024)
Environmental education is vital for promoting pro-environmental behavior, and nature-contact environmental education has progressively emerged as an important form of environmental education. Therefore, exploring the effects and mechanisms of nature-contact environmental education is crucial to enhancing pro-environmental behavior. This manuscript focuses on the Qinling ecological environmental education course at a Chinese university, which exemplifies a form of nature-contact environmental education. The research employs the randomized controlled experimental design as the research methodology. A total of 112 students who participated in the course served as the study sample, with the aim of investigating whether nature-contact environmental education can effectively improve students’ pro-environmental behavior. Additionally, the study also explores the underlying mechanisms driving this effect. The findings indicate that nature-contact environmental education significantly contributes to improving students’ pro-environmental behavior. Furthermore, environmental attitudes and environmental responsibility are identified as key mediators in the relationship between nature-contact environmental education and pro-environmental behavior. These conclusions provide valuable insights for both theoretical research and practical applications of environmental education and pro-environmental behavior.